Elevated Serum Levels of Soluble ST2 Are Associated With Plaque Vulnerability in Patients With Non-ST-Elevation Acute Coronary Syndrome - Luo, Guqing; Qian, Yuxuan; Sheng, Xincheng; Sun, Jiateng; Wu, Zhinan; Liao, Fei; Feng, Qi; Yin, Yan; Ding, Song; Pu, Jun (Frontiers in Cardiovascular Medicine, 2021)
Background: Recent studies have suggested that soluble suppression of tumorigenicity-2 (sST2), an inflammation-related protein receptor, is associated with atherosclerotic diseases. This study aimed to investigate the potential predictive value of sST2 on plaque vulnerability by assessing whether elevated serum levels of sST2 are associated with vulnerable plaque features in patients with non-ST-elevation acute coronary syndrome (ACS). Methods: A total of 120 patients with non-ST-elevation ACS (167 lesions) were prospectively enrolled and evaluated by standard coronary computed tomography angiography (CCTA) and coronary angiography in this study. Serum sST2 levels were measured by ELISA (Presage® ST2 Assay Kit, Critical Diagnostics), and semiautomated software (QAngioCT, Medis) was used to quantify coronary plaques. Results: The included patients were divided into 4 groups by serum sST2 level quartiles. Volumetric analysis of the whole lesion revealed that patients with higher sST2 levels had a larger absolute necrotic core (NC) volume (Quartile 4 vs. Quartile 1, 86.16 ± 59.71 vs. 45.10 ± 45.80 mm3, P = 0.001; Quartile 4 vs. Quartile 2, 86.16 ± 59.71 vs. 50.22 ± 42.56 mm3, P = 0.002) and a higher NC percentage (Quartile 4 vs. Quartile 1, 35.16 ± 9.82 % vs. 23.21 ± 16.18 %, P < 0.001; Quartile 4 vs. Quartile 2, 35.16 ± 9.82 % vs. 22.50 ± 14.03 %, P < 0.001; Quartile 4 vs. Quartile 3, 35.16 ± 9.82 % vs. 25.04 ± 14.48 %, P < 0.001). Correlation analysis revealed that serum sST2 levels were positively correlated with the NC (r = 0.323, P < 0.001) but negatively correlated with dense calcium (r = -0.208, P = 0.007). Furthermore, among those with plaque calcification, patients with spotty calcification exhibited higher serum sST2 levels than those with large calcification (26.06 ± 16.54 vs. 17.55 ± 7.65 ng/mL, P = 0.002). No significant differences in plaque components at the level of the minimal lumen area (MLA) were found among the groups. Conclusions: Serum sST2 levels were correlated with different coronary plaque components in patients with non-ST-elevation ACS. A higher serum level of sST2 was correlated with plaque vulnerability.